Analisis Laporan Keuangan Komersial Melalui Rekonsiliasi Fiskal untuk Mengoptimalkan Perhitungan Pajak Penghasilan Badan pada PT XXX - Aulia, Nabila; Apriliawati, Yeti (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Tax optimization works to achieve the desired profit, but while meeting the appropriate tax obligations. In this study, optimizing the calculation of corporate income tax at PT XXX is carried out using fiscal reconciliation. Previously, the company only calculated Corporate Income Tax based on commercial financial reports and did not make fiscal corrections. The method used in this research is descriptive quantitative, with data collection through interviews and documentation studies. Profit before fiscal reconciliation was recorded at 133,260,638.00. However, after a fiscal reconciliation was carried out, it was found that the corporate income tax at PT XXX increased and became larger with a difference of Rp. 2,821,830.00.